VALUE OF INNOVATION IN LIFELONG LEARNING: PEDAGOGICAL AND SOCIAL CONTEXT - Khilya, Anna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The key competences for lifelong learning have become an integral part of social work and the educational process in Ukraine. Therefore, in this review, we focused on the theoretical aspects of the developed strategies for implementing the competence framework for lifelong learning that are based on the fundamental international documents; analysed the value of this approach for the country's development in general and in specific aspects (based on research and information on the efficiency of implemented projects in this area that are publicly available); and provided a detailed review of the main proposals for the implementation of lifelong learning programmes in the public sector, project activities, and other relevant measures. This made it possible to analyse the main directions of implementation of the relevant state policy, their compliance with the standards and vector of lifelong learning development in international practice, as well as to identify problems and prospects for the development of the Ukrainian state strategy for lifelong learning.